Phytochemical, Antimicrobial and Toxicity Assessment of Dacryodes edulis (G. Don.) H. J. Lam. Leaf Extracts (African Journal of Biomedical Research, 2022)
The leaf of Dacryodes edulis is traditionally used for dressing bruises and wounds; treating diarrhea, dysentery, toothache, gum problems, and tonsillitis. Some of these uses have not been screened scientifically to know its efficacy and safety in consumption. Therefore, this research focused on antimicrobial ability of D. edulis leaf on some selected microorganisms and its toxicity evaluation. The leaf of D. edulis was extracted with methanol and successively partitioned with hexane, ethyl acetate, butanol, and water. Each of the extract was screened for phytochemical constituents using standard methods. They were also tested on twelve microorganisms using standard techniques. Based on performance, acute toxicity test of extracts was conducted on male Wistar rats following standard procedures. Their excised kidneys and livers were histologically examined. Both the leaf methanol extract and fractions contained tannins, anthraquinones, steroids, terpenoids, saponins, alkaloids, phenolics, flavonoids, carotenoids, and cardiac glycosides. The ethyl acetate fraction showed significant zones of inhibition for Klebsiella pneumoniae, Bacillus cereus, Staphylococcus aureus, Serratia marcescens (29, 28, 25, 20 mm, respectively), while the water fraction had 20 mm for Pseudomonas aeruginosa. Some fractions of the leaf also inhibited Trichophyton metagrophytes, Cladosporium herbarum, and Trichoderma species. None of the rats died during the study and the histology of their livers and kidneys showed no lesions at 2900 mg/kg dose. The phytochemical constituents and antibacterial effectiveness of D. edulis leaf extracts supported some traditional uses, while non-toxicity of the leaf extracts showed their safety for use.